Surface damaging of brass and steel pins when sliding over nitrided samples cut by finishing and roughing EDM conditions - Martynenko, V. (2020)
In the forging industry, surface quality and surface treatments of dies are crucial parameters to extend their life. These components are usually machined by milling or by Electrical Discharge Machining (EDM), and the final surface roughness depends on the machining techniques and operational conditions used in its fabrication. After milling, a nitriding treatment is widely applied to extend its service life. Nevertheless, no scientific report that informs about nitriding after EDM has been found. Accordingly, this work focuses on the wear and friction behavior of pins made of brass and medium carbon steel sliding over AISI H13 discs, made by wire EDM in the conditions of finishing and roughing. The discs are plasma nitride, and their effect on the wear during pin-on-disc tests is evaluated. In this sense, the analysis of the surface damage for the different pins will help us to understand the service life and wear evolution of the forging dies. The results show that plasma nitride reduces the friction and prevents the degradation of the pin, independently of the material of the pin, when sliding over finishing and roughing EDM conditions.